STRATEGI IMPLEMENTASI NILAI-NILAI MODERASI BERAGAMA: STUDI KASUS GURU MAN INSAN CENDEKIA OKI - KIAGUS FAISAL (Raudhah - Proud To Be Professional, 2022)
Abstract: Religious moderation values is important to be internalised by teachers in madrasah education. The purpose of this research is to understand teachers' strategies in implementing religious moderation values in MAN Insan Cendekia OKI. To reach the purpose, this research employs case study using questionnaire collection and interview to 10 teacher samples who purposively chosen. Based on the research that has been conducted, the samples has integrated the learning with religious moderation values, conducted practices with hidden curriculum related to religious moderation values, non academic activities, and dormitory activities and religious literacies. Religious moderation values have been integrated by teachers in form of activities and materials. Science and general subject teachers integrated the values during learning activities, and language teachers integrated the values toward the content or learning theme. Meanwhile, dormitory teachers used strategy in integrating moderation values in form of dormitory activities and religious literacy, like Taklim Muta'alim, Safinatun Najah, Aqidatul Awam, Hadith Arbain, and Tafsir book. In conclusion, MAN Insan Cendekia OKI teachers' strategy to strengthen religious moderation values is by adapting in their subjects and dormitory lives (boarding school).